Retaining material
The holding member with a silicone resin and alumina filler addresses temperature-dependent strength issues in electrostatic chucks by reducing pseudo-crosslinking points, ensuring stable performance at high temperatures.
Patent Information
- Application Number
- JP2024017237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-02-07
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-02-07
AI Technical Summary
Existing electrostatic chucks have adhesive members with significant temperature dependence, limiting their use at high temperatures due to variations in strength.
A holding member design with an adhesive member comprising a silicone resin with an aromatic hydrocarbon group in its side chain and a filler primarily composed of alumina, reducing the temperature dependence of the adhesive strength by minimizing pseudo-crosslinking points and increasing the difference in solubility parameters between the resin and filler.
The adhesive member maintains consistent strength across varying temperatures, allowing the holding member to be used effectively at high temperatures without significant strength degradation.
Smart Images

Figure 0007602077000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a retaining member. [Background technology]
[0002] As a holding member for holding an object, an electrostatic chuck that holds the object, a wafer, by electrostatic attraction is known. For example, Patent Documents 1 and 2 disclose an electrostatic chuck that includes a base member made of metal, a ceramic member made of ceramic, and an adhesive member that bonds the base member and the ceramic member. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6611743 [Patent Document 2] Patent No. 6886440 Summary of the Invention [Problem to be solved by the invention]
[0004] However, neither of the techniques in Patent Documents 1 and 2 takes into consideration the need to reduce the temperature dependency of the strength of the adhesive member. If the strength of the adhesive member constituting the holding member is highly temperature dependent, there is a risk that the use of such a holding member will be limited, particularly at high temperatures. For this reason, there has been a demand for the development of a holding member in which the strength of the adhesive member is less temperature dependent.
[0005] The present invention has been made to solve at least part of the above-mentioned problems, and has an object to provide a holding member in which the strength of an adhesive member has little temperature dependency. [Means for solving the problem]
[0006] The present invention has been made to solve at least part of the above-mentioned problems, and can be realized in the following forms.
[0007] (1) According to one aspect of the present invention, there is provided a retaining member comprising a first member, a second member, and an adhesive member that bonds the first member and the second member, where the temperature when the first member and the second member are pulled along a shear direction that shears the adhesive member is defined as a tensile temperature (°C) and the stress generated in the adhesive member when the first member and the second member are pulled along the shear direction is defined as a tensile stress (MPa), the value of the tensile stress (MPa) changes within a range of -0.006 MPa or more and less than 0 MPa for every degree increase in the tensile temperature (°C).
[0008] According to this configuration, it is possible to provide a holding member having an adhesive member whose tensile stress (MPa) value changes within a range of -0.006 MPa or more and less than 0 MPa per degree increase in tensile temperature (°C). In other words, since the temperature dependency of the strength of the adhesive member is small, the strength of the adhesive member is unlikely to decrease even when the holding member is used at high temperatures, so it is possible to provide a holding member that can be used even at high temperatures.
[0009] (2) In the holding member of the above aspect, the adhesive member may contain a silicone resin having an aromatic hydrocarbon group on at least a portion of the side chain. In silicone resins, the interaction between the main chains is large, so that pseudo crosslinking points are formed by the occurrence of minute crystallization and entanglement. If the number of pseudo crosslinking points is large, the number of pseudo crosslinking points that decrease with increasing temperature also increases, so that the temperature dependency of the strength of the adhesive member tends to increase. According to this configuration, since at least a part of the side chain of the silicone resin is provided with an aromatic hydrocarbon group, the occurrence of minute crystallization and entanglement in the main chain of the silicone resin is reduced due to the influence of the steric hindrance of the aromatic hydrocarbon group, and the number of pseudo crosslinking points present in the adhesive member can be reduced. As a result, the number of pseudo crosslinking points that decrease with increasing temperature can also be reduced, so that the temperature dependency of the strength of the adhesive member can be reduced. Also, according to this configuration, since at least a part of the side chain of the silicone resin is provided with an aromatic hydrocarbon group, the hydrophobicity of the silicone resin is increased. Therefore, when the filler contained in the adhesive member is hydrophilic, the difference between the SP value of the silicone resin and the SP value of the hydrophilic filler becomes larger, and the larger this difference in SP values, the fewer the number of pseudo-crosslinking points in the adhesive member, thereby making it possible to reduce the temperature dependence of the strength of the adhesive member.
[0010] (3) In the holding member of the above aspect, the adhesive member may contain a filler containing alumina as a main component. According to this configuration, the main component of the filler is highly hydrophilic alumina, so that when the resin contained in the adhesive member is highly hydrophobic, the difference between the SP value of the resin and the SP value of the filler becomes large, and the larger the difference in SP value, the fewer the number of pseudo crosslinking points in the adhesive member, so that the temperature dependency of the strength of the adhesive member can be reduced.
[0011] (4) In the retaining member of the above aspect, the adhesive member may contain a silicone resin and a filler, and the filler may contain 2 parts by weight or more and 15 parts by weight or less of carbon black per 100 parts by weight of the silicone resin. According to this configuration, even if the holding member is exposed to high temperatures for a long period of time, the hardening of the adhesive member and the increase in the elastic modulus of the adhesive member can be suppressed, and therefore it is possible to provide a holding member that can be used even at high temperatures without the material of the adhesive member undergoing significant changes.
[0012] The present invention can be realized in various forms, for example, in the form of an electrostatic chuck or a vacuum chuck comprising the above-mentioned adhesive member, a semiconductor manufacturing apparatus or a ceramic heater comprising the above-mentioned adhesive member, parts comprising these, and methods for manufacturing these, etc. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is an explanatory diagram illustrating a cross-sectional configuration of a holding member according to an embodiment of the present invention. [Diagram 2] FIG. 1 is an explanatory diagram for explaining an SP value. [Diagram 3] FIG. 11 is an explanatory diagram showing the results of evaluating the performance of adhesive members. [Figure 4] FIG. 2 is an explanatory diagram of a test piece used for evaluating the performance of an adhesive member. [Diagram 5] FIG. 1 is an explanatory diagram showing test results when tensile stress was measured using a test piece. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] FIG. 1 is an explanatory diagram showing a schematic cross-sectional configuration of a holding member 1 according to an embodiment of the present invention. The holding member 1 is an electrostatic chuck that attracts and holds a semiconductor wafer W, which is an object, by electrostatic attraction. The arrow shown in FIG. 1 indicates the direction in which the semiconductor wafer W is attracted to the holding member 1. The holding member 1 is used, for example, to fix the semiconductor wafer W in a vacuum chamber of a semiconductor manufacturing device. The holding member 1 includes a ceramic member 10, a base member 20, an adhesive member 30, an electrostatic electrode 40, and a heater electrode 50.
[0015] The ceramic member 10 is a disk-shaped member and is made of ceramics. Examples of materials for forming the ceramic member 10 include aluminum oxide (alumina, Al2O3) and aluminum nitride (AlN), and in this embodiment, the ceramic member 10 is made of alumina. The ceramic member 10 has an adsorption surface 10f. The adsorption surface 10f is a circular surface on the side that adsorbs the semiconductor wafer W.
[0016] The base member 20 is a disk-shaped member having a larger diameter than the ceramic member 10, and is made of metal or various composite materials. The metal forming the base member 20 is preferably Al (aluminum), Ti (titanium), or an alloy thereof. The composite material forming the base member 20 is preferably a composite material obtained by melting and pressurizing an aluminum alloy mainly composed of aluminum into a porous ceramic mainly composed of silicon carbide (SiC). The aluminum alloy contained in the composite material may contain Si (silicon) or Mg (magnesium), or may contain other elements as long as they do not affect the properties, etc.
[0017] A coolant flow path 21 is formed inside the base member 20. When a coolant (e.g., a fluorine-based inert liquid or water) flows through the coolant flow path 21, the base member 20 is cooled. At this time, the ceramic member 10 is also cooled by heat transfer (heat withdrawal) between the base member 20 and the ceramic member 10 via the adhesive member 30, and the semiconductor wafer W adsorbed to the adsorption surface 10f of the ceramic member 10 is also cooled.
[0018] The adhesive member 30 is disposed between the ceramic member 10 and the base member 20, and bonds the ceramic member 10 and the base member 20. The ceramic member 10 and the base member 20 correspond to a first member and a second member bonded to each other via the adhesive member 30. The first member and the second member are used to refer to members bonded to each other via the adhesive member. The adhesive member 30 contains a silicone resin having a phenyl group as an aromatic hydrocarbon group in at least a part of the side chain. In this embodiment, the silicone resin contains 5 mol% of phenyl groups. The adhesive member 30 also contains a filler whose main component is alumina. The main component refers to the component with the highest volumetric content.
[0019] The electrostatic electrode 40 is a disk-shaped member provided inside the ceramic member 10, and is made of a conductive material such as tungsten or molybdenum. The electrostatic electrode 40 generates an electrostatic attractive force on the attraction surface 10f when power is supplied from an external power source (not shown). The semiconductor wafer W is attracted toward the attraction surface 10f by this electrostatic attractive force, and is thereby held on the attraction surface 10f.
[0020] The heater electrode 50 is provided inside the ceramic member 10 and is made of a conductive material such as tungsten or molybdenum. The heater electrode 50 generates heat when power is supplied from an external power source (not shown). This heat warms the ceramic member 10, and the semiconductor wafer W attracted to the attracting surface 10f of the ceramic member 10 is also heated.
[0021] FIG. 2 is an explanatory diagram for explaining the SP value. The SP value is a solubility parameter, and is an index that indicates the hydrophilicity or hydrophobicity of a substance. A substance with a large SP value is highly hydrophilic, and a substance with a small SP value is highly hydrophobic. The double-headed arrows shown in each of FIGS. 2(A) to (C) indicate the difference in SP value for the silicone resin and the filler contained in the adhesive member. In detail, the further to the left the left arrowhead of the double-headed arrow is, the smaller the SP value of the silicone resin in the adhesive member is, and the further to the right the right arrowhead is, the larger the SP value of the filler in the adhesive member is.
[0022] Of the double-headed arrows in FIG. 2(A), the left arrowhead indicates the SP value of the silicone resin (having a phenyl group in part of the side chain) contained in the adhesive member 30, and the right arrowhead indicates the SP value of the filler (mainly made of alumina) contained in the adhesive member 30. That is, FIG. 2(A) shows the difference in SP value for the silicone resin and filler contained in the adhesive member 30 of this embodiment. In contrast, FIGS. 2(B) and (C) show the difference in SP value for the silicone resin and filler contained in the adhesive member of the comparative example. In detail, of the double-headed arrows in FIG. 2(B), the left arrowhead indicates the SP value of the silicone resin (having no phenyl group in the side chain), and the right arrowhead indicates the SP value of the filler (mainly made of alumina). Of the double-headed arrows in FIG. 2(C), the left arrowhead indicates the SP value of the silicone resin (having a phenyl group in part of the side chain) contained in the adhesive member 30, and the right arrowhead indicates the SP value of the filler (mainly made of aluminum nitride). 2(A) to 2(C), the adhesive member 30 of this embodiment has a larger difference between the SP value of the silicone resin and the SP value of the filler compared to the adhesive member of the comparative example. The larger the difference in SP value, the lower the mutual affinity, and the fewer the number of pseudo crosslinking points in the adhesive member. The pseudo crosslinking points are crosslinking points formed pseudo in the silicone resin due to the occurrence of minute crystallization and entanglement due to the strong interaction between the main chains of the silicone resin.
[0023] If the number of pseudo cross-linking points is large, the number of pseudo cross-linking points that decreases with increasing temperature also increases, so the strength of the adhesive member tends to become more temperature-dependent. The reason for this is explained using the following formula (1) for calculating the rigidity modulus G of the target substance. In formula (1), ρ is density, R is the gas constant, T is absolute temperature, M x is the molecular weight between crosslinking points. G=ρRT / M x …(1)
[0024] First, if there are many cross-linking points in the target substance, the molecular weight M x decreases, and so the modulus of rigidity increases according to formula (1). Qualitatively, when there are many crosslinks, the modulus of rigidity is large and the material becomes hard, and large stress occurs with small strain, so the tensile stress at break increases. On the other hand, when the number of pseudo crosslinks in the target material decreases with increasing temperature, the molecular weight M between the crosslinks increases. x As shown in formula (1), the molecular weight between crosslinks, M x As the SP value of the silicone resin increases, the rigidity modulus G decreases. When the number of pseudo crosslinking points in the target substance is large, the number of pseudo crosslinking points that decrease with increasing temperature also increases, and the temperature dependency of the strength of the adhesive member becomes greater. Therefore, if the number of pseudo crosslinking points in the adhesive member is reduced by increasing the difference between the SP value of the silicone resin and the SP value of the filler, the temperature dependency of the strength of the adhesive member becomes smaller.
[0025] FIG. 3 is an explanatory diagram showing the results of evaluating the performance of the adhesive member. First, each item shown in "Material" in FIG. 3 will be explained. "○" in the "Silicone resin" row indicates that the silicone resin contained in the adhesive member has a phenyl group in a part of the side chain of the silicone resin, and "×" in the "Silicone resin" row indicates that the silicone resin does not have a phenyl group in the side chain. The "Filler type" row indicates the type of filler contained in the adhesive member. With regard to the type of filler, Al2O3 is alumina, CB is carbon black, and AlN is aluminum nitride. The "Filler amount" row refers to the volume part of the filler in the adhesive member when the entire adhesive member is taken as 100 volume parts. As shown in FIG. 3, the adhesive members of Examples 1 and 2 and the adhesive members of Comparative Examples 1 to 4 all contain 44 volume parts of filler and 56 volume parts of silicone resin. The "Parts by weight of carbon black" row refers to the parts by weight of carbon black relative to 100 parts by weight of silicone resin contained in the adhesive member. The adhesive members of Examples 1 and 2 correspond to the adhesive member 30 constituting the retaining member 1 described above, and the adhesive member of Example 2 differs from the adhesive member of Example 1 only in that the filler contains carbon black.
[0026] Next, each item shown in "Physical Properties" in FIG. 3 will be described. First, "Performance Evaluation 1" will be described. In "Performance Evaluation 1", as shown in FIG. 4, a test piece TP1 is used in which one end side surfaces of two plate-like members (a first member 201 and a second member 202) are bonded together with an adhesive member 30G (a general term for the adhesive members of Examples 1 and 2 and the adhesive members of Comparative Examples 1 to 4). Using this test piece TP1, the temperature when the first member 201 and the second member 202 are pulled along the shear direction SD that shears the adhesive member 30G is defined as the tensile temperature (°C), and the stress generated in the adhesive member 30G when the first member 201 and the second member 202 are pulled along the shear direction SD is defined as the tensile stress (MPa). In detail, the tensile stress (MPa) is calculated by dividing the load (N) when the test piece TP1 is pulled to break by the adhesive area. In "Performance Evaluation 1", it was evaluated whether the value of tensile stress (MPa) changes within the range of -0.006 MPa or more and less than 0 MPa per 1 degree increase in tension temperature (℃). That is, "○" in the row of "Performance Evaluation 1" indicates that the value of tensile stress (MPa) changes within the range of -0.006 MPa or more and less than 0 MPa per 1 degree increase in tension temperature, and "×" in the row of "Performance Evaluation 1" indicates that the value of tensile stress (MPa) does not change within the range of -0.006 MPa or more and less than 0 MPa per 1 degree increase in tension temperature. Details will be described with reference to Figures 5(A) to (D).
[0027] 5(A) to (D) are explanatory diagrams showing test results when the tensile stress (MPa) was measured using the test piece TP1. In FIG. 5(A) to (D), the horizontal axis indicates the temperature (°C) during tension, and the vertical axis indicates the tensile stress (MPa). The results shown in FIG. 5(A) to (D) are the results when the first member 201 and the second member 202 were pulled along the shear direction that shears the adhesive member 30 at a tension speed of 2 mm / min with reference to JIS K6850. In this case, in the results shown in FIG. 5(A) to (D), the first member 201 and the second member 202 are plate-like members with a width of 12.5 mm × length of 100 mm × thickness of 1 mm, and the test piece TP1 is a test piece in which one end side surface of each of the first member 201 and the second member 202 is bonded, measuring 12.5 mm × 12.5 mm. The bonding conditions here are appropriately adjusted depending on the bonding member used so as to obtain the desired bonding properties, and for example, the bonding member 30 is sandwiched between the first member 201 and the second member 202, heated at 100°C for 72 hours, and then further heated at 140°C for 10 hours to produce a test piece TP1. As a measuring device for measuring the tensile stress (MPa), a known tensile tester or strength tester can be used, for example, Autograph AGS-5kNX manufactured by Shimadzu Corporation.
[0028] FIG. 5(A) shows the test results of measuring the tensile stress (MPa) of the test piece TP1 produced using the adhesive member of Example 1. Line segment La1 shows the test results of the test piece TP1 in which the first member 201 and the second member 202 are bonded by the adhesive member of Example 1 having a thickness of 200 μm. Line segment La2 shows the test results of the test piece TP1 in which the first member 201 and the second member 202 are bonded by the adhesive member of Example 1 having a thickness of 700 μm. Line segments La1 and La2 correspond to a regression line obtained by the least squares method from a plurality of measurement data obtained when measuring the tensile stress (MPa) of the test piece TP1 using the adhesive member of Example 1. The same applies to lines Lb1 and Lb2, line segment Lc, and line segments Ld1 to Ld3 in the following FIGS. 5(B) to (D).
[0029] FIG. 5(B) shows the test results of measuring the tensile stress (MPa) of the test piece TP1 produced using the adhesive member of Comparative Example 1. The line segment Lb1 shows the test results of the test piece TP1 in which the first member 201 and the second member 202 are bonded by the adhesive member of Comparative Example 1 having a thickness of 200 μm. The line segment Lb2 shows the test results of the test piece TP1 in which the first member 201 and the second member 202 are bonded by the adhesive member of Comparative Example 1 having a thickness of 700 μm. FIG. 5(C) shows the test results of measuring the tensile stress (MPa) of the test piece TP1 produced using the adhesive member of Comparative Example 2. The line segment Lc shows the test results of the test piece TP1 in which the first member 201 and the second member 202 are bonded by the adhesive member of Comparative Example 2 having a thickness of 700 μm.
[0030] 5(D) shows the test results of measuring the tensile stress (MPa) of the test piece TP1 produced using the adhesive member of Comparative Example 4. The line segment Ld1 shows the test results of the test piece TP1 in which the first member 201 and the second member 202 are bonded by the adhesive member of Comparative Example 4 having a thickness of 200 μm. The line segment Ld2 shows the test results of the test piece TP1 in which the first member 201 and the second member 202 are bonded by the adhesive member of Comparative Example 4 having a thickness of 300 μm. The line segment Ld3 shows the test results of the test piece TP1 in which the first member 201 and the second member 202 are bonded by the adhesive member of Comparative Example 4 having a thickness of 500 μm.
[0031] When comparing the test results when the adhesive member 30G had a thickness of 200 μm, the slope of the line segment La1 was −0.0071, the slope of the line segment Lb1 was −0.011, and the slope of the line segment Ld1 was −0.0086. That is, the adhesive member of Example 1 has smaller temperature dependence of strength than the adhesive members of Comparative Example 1 and Comparative Example 4.
[0032] A multiple regression analysis was performed on multiple measurement data used to obtain each line segment in Figures 5(A), 5(B), and 5(D), to create a prediction formula for the tensile stress (MPa) of the adhesive member of Example 1, the adhesive member of Comparative Example 1, and the adhesive member of Comparative Example 4. When the tensile stress (MPa) was Ts, the thickness of the adhesive member was Th (μm), and the temperature during tension was Te (°C), the prediction formula for Ts was as follows. Adhesive member of Example 1: Ts = -0.0015Th - 0.0052Te + 2.8387 Adhesive member of Comparative Example 1: Ts=-0.0027Th-0.0071Te+3.7062 Adhesive member of Comparative Example 4: Ts = -0.0023Th -0.0073Te +3.7143
[0033] Regarding the prediction formula of the adhesive member of Example 1, when the value of Th is constant, the value of Ts changes by -0.0052 for every increase in the value of Te by 1. That is, the value of the tensile stress (MPa) changes by -0.0052 MPa for every increase in the tensile temperature (°C) by 1 degree (changes within the range of -0.006 MPa or more and less than 0 MPa). On the other hand, regarding the prediction formula of the adhesive member of Comparative Example 1 (Comparative Example 4), when the value of Th is constant, the value of Ts changes by -0.0071 (-0.0073) for every increase in the value of Te by 1. That is, the value of the tensile stress (MPa) does not change within the range of -0.006 MPa or more and less than 0 MPa. In this way, "Performance Evaluation 1" is an evaluation based on the coefficient value of the tensile temperature (Te) in the prediction formula of the tensile stress (Ts) created by multiple regression analysis with the thickness (Th) of the adhesive member and the tensile temperature (Te) as explanatory variables. In other words, if the adhesive member contained in the test piece TP1 is different, the coefficient of the adhesive member thickness (Th), the coefficient of the tensile temperature (Te), and the intercept value in the prediction equation for Ts will all be different, and "Performance Evaluation 1" is performed based on the value of the coefficient of the tensile temperature (Te).
[0034] For example, when "Performance Evaluation 1" of the adhesive member 30 already included in the holding member 1 (FIG. 1) described above is performed, it is performed in the following steps. First, a portion including the ceramic member 10, the base member 20, and the adhesive member 30 is cut out from the holding member 1, and a test piece TP1 (FIG. 4) is prepared from the cut out portion. At this time, the ceramic member 10 and the base member 20 correspond to the first member 201 and the second member 202 in the test piece TP1. Next, the tensile stress (MPa) at various tensile temperatures (°C) is measured using the prepared test piece TP1 to obtain multiple measurement data, and then a prediction formula for the tensile stress (Ts) is created from the multiple measurement data by multiple regression analysis using the thickness (Th) of the adhesive member and the tensile temperature (Te) as explanatory variables. Then, "Performance Evaluation 1" is performed based on the coefficient value of the tensile temperature (Te) in the prediction formula. The shape of the test piece for performing "Performance Evaluation 1" is not limited to the shape of the test piece TP1, and may be any shape as long as the first member 201 and the second member 202 bonded via the adhesive member 30 can be pulled along the shear direction SD. Of course, the thickness of the adhesive member 30 may also be any thickness.
[0035] Next, "Performance Evaluation 2" will be described. "Performance Evaluation 2" is a performance evaluation when the heat resistance life is measured. In "Performance Evaluation 2", whether the adhesive member 30G is difficult to harden when exposed to high temperatures for a long time was evaluated. That is, "○" in the "Performance Evaluation 2" row indicates that it is difficult to harden when exposed to high temperatures for a long time, and "◎" in the "Performance Evaluation 2" row indicates that it is even more difficult to harden when exposed to high temperatures for a long time. When the adhesive member 30G hardens, the amount of distortion of the adhesive member 30G decreases.
[0036] The strain amount, which is an index of hardening, can be evaluated by pulling the first member 201 and the second member 202 along the shear direction SD that shears the adhesive member 30G at room temperature at a tensile speed of 2 mm / min, with reference to JIS K6850, as in "Performance Evaluation 1". The shear strain (%) is calculated by dividing the strain amount δ (mm) at break by the thickness (mm) of the adhesive member 30G. The test piece used to evaluate the strain amount is a test piece in which one end surface of each of the first member 201 and the second member 202, which are plate-like members with a width of 12.5 mm, a length of 100 mm, and a thickness of 1 mm, is bonded, measuring 12.5 mm x 12.5 mm, like the test piece TP1 from which the results of Figures 5(A) to (D) were obtained. The bonding conditions here are appropriately adjusted depending on the bonding member used so as to obtain the desired bonding properties, and for example, a test piece used for evaluating the amount of strain can be prepared by sandwiching the bonding member 30 between the first member 201 and the second member 202, heating at 100°C for 72 hours, and then further heating at 140°C for 10 hours. A known tensile tester or strength tester can be used as a measuring device for measuring the amount of strain, and an example of such a measuring device is the Autograph AGS-5kNX manufactured by Shimadzu Corporation.
[0037] "Performance Evaluation 2" can be evaluated by examining the rate of change in shear strain in the test piece before and after heating using the test piece prepared by the above procedure. Here, the test piece after heating refers to the test piece after heating at 180°C for 3000 hours. When the shear strain of the test piece before heating (at room temperature) is γ0, the shear strain of the test piece after heating is γ1, and (γ1-γ0) / γ0 is the rate of change in shear strain, the performance evaluation is "◎" when the rate of change is -0.2 or more and less than 0.2, and when the rate of change is -0.5 or more and less than -0.2, or when the rate of change is 0.2 or more and less than 0.5, the performance evaluation is "◯". Note that when the rate of change is less than -0.5 or 0.5 or more, the performance evaluation is "×".
[0038] For example, when "Performance Evaluation 2" of the adhesive member 30 already included in the holding member 1 (FIG. 1) described above is performed, the following steps are performed. First, a portion including the ceramic member 10, the base member 20, and the adhesive member 30 is cut out from the holding member 1, and a test piece is prepared from the cut out portion by the above-mentioned procedure. Before evaluating the amount of strain, the thickness of the adhesive member 30 in the cut out test piece is measured. Using the measured test piece, "Performance Evaluation 2" can be performed. The shape of the test piece for performing "Performance Evaluation 2" is not limited to the shape of the test piece prepared by the above-mentioned procedure, and may be any shape as long as the first member 201 and the second member 202 bonded via the adhesive member 30 can be pulled along the shear direction SD. In addition, the holding member 1 (electrostatic chuck) from which the test piece to be applied to "Performance Evaluation 2" is cut out is not limited to a new one, and may have been in use for a certain period of time. Regardless of the holding member 1, the point of acquisition is considered to be in an unheated state, and from that point on, it is heated at 180°C for 3000 hours to obtain the value of γ1, thereby making it possible to confirm the rate of change in shear strain.
[0039] 3, as a result of evaluating each of the adhesive members of Examples 1 and 2 and the adhesive members of Comparative Examples 1 to 4, only the adhesive members of Examples 1 and 2 were given a grade of "Good" in "Performance Evaluation 1." The reason why the adhesive members of Examples 1 and 2 (corresponding to the adhesive member 30 constituting the holding member 1 described above) were given a grade of "Good" in "Performance Evaluation 1" is believed to be that all of the adhesive members contained a silicone resin having a phenyl group (5 mol%) as an aromatic hydrocarbon group in part of the side chain, and a filler mainly composed of alumina.
[0040] As shown in Fig. 3, only the adhesive member of Example 2 and the adhesive member of Comparative Example 2 were given a "◎" in "Performance Evaluation 2". The reason why these adhesive members received a "◎" in "Performance Evaluation 2" is believed to be because the filler in each adhesive member contained carbon black. In detail, the filler in each adhesive member contained 5 parts by weight of carbon black per 100 parts by weight of silicone resin.
[0041] In the adhesive member 30 (adhesive members of Examples 1 and 2) included in the holding member 1 of the embodiment described above, the value of the tensile stress (MPa) changes within a range of -0.006 MPa or more and less than 0 MPa for every degree increase in the tensile temperature (°C). In other words, since the temperature dependency of the strength of the adhesive member 30 is small, the strength of the adhesive member 30 is unlikely to decrease even in a situation where the holding member 1 is used at high temperatures, a holding member 1 that can be used even at high temperatures can be provided.
[0042] Moreover, the adhesive member 30 (the adhesive member of Examples 1 and 2) included in the holding member 1 contains a silicone resin having a phenyl group as an aromatic hydrocarbon group in a part of the side chain. Therefore, the occurrence of micro-crystallization and entanglement in the main chain of the silicone resin due to the influence of the steric hindrance of the aromatic hydrocarbon group is reduced, and the number of pseudo crosslinking points present in the adhesive member 30 can be reduced. As a result, the number of pseudo crosslinking points that decrease when the temperature rises can also be reduced, so that the temperature dependency of the strength of the adhesive member 30 can be reduced. In addition, since the side chain of the silicone resin included in the adhesive member 30 is provided with an aromatic hydrocarbon group (5 mol % phenyl group), the hydrophobicity of the silicone resin is increased, and the main component of the filler included in the adhesive member 30 is alumina with high hydrophilicity (see FIG. 2(A)). Therefore, the difference between the SP value of the silicone resin and the SP value of the filler becomes larger, and the larger the difference in the SP value, the lower the affinity between the silicone resin and the filler, and the fewer the number of pseudo crosslinking points in the adhesive member 30, so that the temperature dependency of the strength of the adhesive member 30 can be reduced.
[0043] Furthermore, as shown in the adhesive member of Example 2 in Fig. 3, when the filler in the adhesive member 30 contains carbon black, even if the holding member 1 is exposed to high temperatures for a long period of time, the hardening of the adhesive member 30 and the increase in the elastic modulus of the adhesive member 30 can be suppressed. Therefore, it is possible to provide a holding member 1 that can be used even at high temperatures without the material of the adhesive member 30 changing significantly. It has been confirmed through experiments that it is preferable for the silicone resin to contain 2 parts by weight or more and 15 parts by weight or less of carbon black per 100 parts by weight of silicone resin.
[0044] <Modifications of this embodiment> The present invention is not limited to the above-described embodiment, and can be embodied in various forms without departing from the spirit and scope of the invention. For example, the following modifications are also possible.
[0045] In the above embodiment, the silicone resin in the adhesive member 30 contains 5 mol % of phenyl groups, but is not limited thereto. The proportion of phenyl groups contained in the silicone resin may be any proportion, and is preferably within a range of 3 mol % or more and 16 mol % or less. In the above embodiment, the silicone resin in the adhesive member 30 has phenyl groups in at least a part of its side chain, but is not limited thereto. For example, the side chain of the silicone resin may have an aryl group such as a tolyl group, a xylyl group, or a naphthyl group instead of or in addition to the phenyl group. Of course, it is preferable that the side chain of the silicone resin has at least a phenyl group.
[0046] In the above embodiment, the filler in the adhesive member 30 contains carbon black, but is not limited to this. For example, the filler may contain carbon powder such as carbon fiber, carbon nanotube, and graphene instead of or in addition to carbon black. Of course, it is preferable that the filler contains at least carbon black.
[0047] In the above embodiment, the adhesive member 30 includes a silicone resin and a filler, but is not limited thereto. The adhesive member 30 may include other components in addition to the silicone resin and the filler. Examples of the other components include a filler, a reaction inhibitor, and a viscosity adjuster.
[0048] Although the present aspect has been described above based on the embodiment and modified examples, the above-mentioned embodiment of the aspect is intended to facilitate understanding of the present aspect and does not limit the present aspect. The present aspect may be modified or improved without departing from the spirit and scope of the claims, and equivalents are included in the present aspect. Furthermore, if a technical feature is not described as essential in this specification, it may be deleted as appropriate.
[0049] The present invention can also be realized in the following forms. [Application example 1] A holding member, A first member; A second member; an adhesive member that adheres the first member and the second member, A retaining member, characterized in that when the temperature when the first member and the second member are pulled along a shear direction that shears the adhesive member is defined as the tensile temperature (°C), and the stress generated in the adhesive member when the first member and the second member are pulled along the shear direction is defined as the tensile stress (MPa), the value of the tensile stress (MPa) changes within a range of -0.006 MPa or more and less than 0 MPa for every degree increase in the tensile temperature (°C). [Application example 2] The holding member according to Application Example 1, A holding member, wherein the adhesive member contains a silicone resin having an aromatic hydrocarbon group on at least a portion of the side chain. [Application example 3] The holding member according to Application Example 1 or Application Example 2, A holding member, wherein the adhesive member contains a filler whose main component is alumina. [Application example 4] The holding member according to any one of Application Examples 1 to 3, The adhesive member includes a silicone resin and a filler, The retaining member, wherein the filler contains 2 parts by weight or more and 15 parts by weight or less of carbon black with respect to 100 parts by weight of the silicone resin. [Explanation of symbols]
[0050] 1...Retaining member 10...Ceramics components 10f…Adsorption surface 20...Base member 21... Coolant flow path 30, 30G…Adhesive material 40...Electrostatic electrode 50…Heater electrode 201, 301…First member 202, 302…Second member
Claims
1. A retaining member, A first member; A second member; and an adhesive member that bonds the first member and the second member, When the temperature when the first member and the second member are pulled along a shear direction in which the adhesive member is sheared is defined as a tensile temperature (°C) and the stress generated in the adhesive member when the first member and the second member are pulled along the shear direction is defined as a tensile stress (MPa), the value of the tensile stress (MPa) changes within a range of -0.006 MPa or more and less than 0 MPa for each degree increase in the tensile temperature (°C), The value of the tensile stress (MPa) is a coefficient of the tensile temperature (°C) in a prediction equation for the tensile stress (MPa) created by multiple regression analysis using the thickness of the adhesive member and the tensile temperature (°C) as explanatory variables.
2. 2. The holding member according to claim 1, A holding member, wherein the adhesive member contains a silicone resin having an aromatic hydrocarbon group on at least a portion of the side chain.
3. The holding member according to claim 1 or 2, A holding member, wherein the adhesive member contains a filler whose main component is alumina.
4. The holding member according to claim 1 or 2, The adhesive member includes a silicone resin and a filler, The retaining member, wherein the filler contains 2 parts by weight or more and 15 parts by weight or less of carbon black relative to 100 parts by weight of the silicone resin.
5. A retaining member according to claim 1 or claim 2, A retaining member characterized in that, regarding a shear strain calculated by dividing the amount of strain when the first member and the second member are pulled along the shear direction to break by the thickness of the adhesive member, when the shear strain at room temperature is defined as γ0, the shear strain after heating at 180°C for 3000 hours is defined as γ1, and (γ1-γ0) / γ0 is defined as a rate of change of the shear strain, the value of the rate of change is -0.5 or more and less than 0.5.
Citation Information
Patent Citations
Composite member and adhesive composition
JP2020023088A
Composite member and adhesive composition
JP2020026116A
Holding device and composite member
JP2023060542A
Composite materials
JP6611743B2
Composite member and adhesive composition
JP6886440B2
